A complementary approach for detecting biological signals through a semi-automated feature selection tool - Arini, Gabriel Santos; Mencucini, Luiz Gabriel Souza; de Felício, Rafael; Feitosa, Luís Guilherme Pereira; Rezende-Teixeira, Paula; de Oliveira Tsuji, Henrique Marcel Yudi; Pilon, Alan Cesar; Pinho, Danielle Rocha; Costa Lotufo, Letícia Veras; Lopes, Norberto Peporine; Trivella, Daniela Barretto Barbosa; da Silva, Ricardo Roberto (Frontiers in Chemistry, 2024)
Introduction Untargeted metabolomics is often used in studies that aim to trace the metabolic profile in a broad context, with the data-dependent acquisition (DDA) mode being the most commonly used method. However, this approach has the limitation that not all detected ions are fragmented in the data acquisition process, in addition to the lack of specificity regarding the process of fragmentation of biological signals. The present work aims to extend the detection of biological signals and contribute to overcoming the fragmentation limits of the DDA mode with a dynamic procedure that combines experimental and in silico approaches. Methods Metabolomic analysis was performed on three different species of actinomycetes using liquid chromatography coupled with mass spectrometry. The data obtained were preprocessed by the MZmine software and processed by the custom package RegFilter. Results and Discussion RegFilter allowed the coverage of the entire chromatographic run and the selection of precursor ions for fragmentation that were previously missed in DDA mode. Most of the ions selected by the tool could be annotated through three levels of annotation, presenting biologically relevant candidates. In addition, the tool offers the possibility of creating local spectral libraries curated according to the user’s interests. Thus, the adoption of a dynamic analysis flow using RegFilter allowed for detection optimization and curation of potential biological signals, previously absent in the DDA mode, being a good complementary approach to the current mode of data acquisition. In addition, this workflow enables the creation and search of in-house tailored custom libraries.